2020
DOI: 10.3390/polym12051014
|View full text |Cite
|
Sign up to set email alerts
|

p66shc siRNA-Encapsulated PLGA Nanoparticles Ameliorate Neuropathic Pain Following Spinal Nerve Ligation

Abstract: p66shc, a member of the shc adaptor protein family, has been shown to participate in regulation of mitochondrial homeostasis, apoptosis, and autophagosome formation. The present study was performed to investigate whether p66shc siRNA-encapsulated poly(d,l-lactic-co-glycolic acid) nanoparticles (p66shc siRNA-PLGA NPs) can attenuate spinal nerve ligation (SNL)-induced neuropathic pain in rats. The SNL-induced pain behavior was decreased in the p66shc siRNA-PLGA NP-treated group compared with the scrambled siRNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“… 45 , 46 P66shc has been shown to participate in the regulation of mitochondrial homeostasis in NP cells and play an important role in IVDD. 47 (Figure 2 ).…”
Section: Relationships Between Mitochondria and Rosmentioning
confidence: 99%
See 1 more Smart Citation
“… 45 , 46 P66shc has been shown to participate in the regulation of mitochondrial homeostasis in NP cells and play an important role in IVDD. 47 (Figure 2 ).…”
Section: Relationships Between Mitochondria and Rosmentioning
confidence: 99%
“…Moderate levels of mitochondrial ROS can activate the antioxidant compensation mechanism, protecting organelles from the harmful effects of ROS and ultimately achieving metabolic balance. 47 However, when external conditions change, increased ROS production can induce mitochondrial membrane depolarization. Oxidative stress is induced when excessive ROS production outpaces antioxidant defenses.…”
Section: Relationships Between Mitochondria and Rosmentioning
confidence: 99%
“… 142 Intrathecal treatments with C‐X3‐C motif chemokine receptor 1 (CX3CR1), p38, p66shc siRNA encapsulated PLGA nanoparticles, or forkhead box P3 (Foxp3) plasmid‐encapsulated PLGA nanoparticles inhibit microglial activation and hyperalgesia in SNL rats. 141 , 143 , 144 , 145 …”
Section: Challenges and Considerations In Delivering Mirna‐and Lncrna...mentioning
confidence: 99%
“…Results demonstrated that the NPs were less toxic and had a two-fold antioxidant activity compared to the pure drug. 60 Four similar studies investigated the benefit of PLGA NPs for alleviating pain in rat models of spinal nerve ligation (performed at L5) using Sprague-Dawley rats, by loading PLGA NPs with Foxp3 plasmid, 61 p66shc siRNA, 62 p38 siRNA 63 and encapsulating PLGA with CX3CR1 siRNA, 64 respectively. All four studies indicated that the use of the aforementioned PLGA NPs effectively reduced neuropathic pain in SNL-induced rats by reducing microglial activity and expression of proinflammatory mediators.…”
Section: Plga Nps In Tsci Modelsmentioning
confidence: 99%